Regresi Logistik Multinomial terhadap Faktor Pemanfaatan Jaminan Kesehatan Pasien Rawat Jalan Provinsi Bali 2023 - Ni Luh Gede Arun Dayanti Purwa; Made Susilawati; IPW Gautama; Ni Luh Putu Suciptawati; Eka N Kencana; Ketut Jayanegara (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Public health is one of the indicators used to measure a country's level of welfare. In the 2020–2024 National Medium-Term Development Plan (RPJMN), the government targets Universal Health Coverage (UHC) through health insurance programs. The utilization of health insurance can be influenced by various individual characteristics. This study aims to analyze the factors influencing the utilization of health insurance during outpatient care in Bali Province, using data from the March 2023 Susenas survey. In this study, a multinomial logistic regression model was used, with the dependent variable categorized into not using, BPJS PBI, and BPJS non-PBI. The independent variables analyzed include age, gender, marital status, education level, employment status, regional typology, and outpatient visit frequency. The analysis results showed that the model's accuracy was 61.63%, with significant variables including age, marital status, education level, employment status, regional typology, and frequency of outpatient care. These findings indicate that individual characteristics play a significant role in determining the utilization and type of health insurance used.